Littoral macrozoobenthos communities of the Kuibyshev Reservoir in the area of Kazan - G.S. Tarasov; O.I. Khamitov; L.A. Frolova (Учёные записки Казанского университета: Серия Естественные науки)
The qualitative and quantitative characteristics of benthic communities in the shore area and shallow waters of the Volga reach of the Kuibyshev Reservoir near the village of Staroe Arakchino (Kazan) were studied during the growing season of 2015. A total of 27 hydrobiont taxa belonging to three types of invertebrate organisms were registered. The taxonomic composition of benthic communities was compared for the year of the study and previous years. A decrease in the values of the quantitative characteristics of macrozoobenthos was revealed: a decline in the average abundance and biomass was observed in 2010–2015. The main groups of invertebrates that mostly contribute to the abundance of the population were dominant invasive species, such as Dreissena polymorpha (Pallas, 1771) and Lithoglyphus naticoides (Pfeiffer, 1828). The biomass was determined by large bivalve and gastropod mollusks: Unio longirostris (Rossmaessler, 1836), Pseudanodonta complanata (Rossmaessler, 1835), Viviparus viviparus (L., 1758), V. contectus (Millet, 1813), and L. auricularia (L., 1758). Soft zoobenthos played an important role in terms of the abundance and biomass only in the area of shallow waters and was represented by chironomids (Chironomus sp. (Meigen, 1803)) and heteropterans (I. cimicoides (L., 1758) and Micronecta sp. (Kirkaldy, 1897)).